2014
DOI: 10.1007/s00520-014-2333-x
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life characteristics and palliative care provision for elderly patients suffering from acute myeloid leukemia

Abstract: Elderly AML patients carry dismal prognosis with their final phase of disease mostly hospitalized in acute care settings. Infections and bleeding could complicate course of illness and lead to rapid deterioration. PC collaboration remains important in psychosocial support and coverage of dying AML patients in non-hospice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 20 publications
5
43
0
Order By: Relevance
“…More than 80% were hospitalized in the last 30 days of their life and only a minority of them had received palliative care or hospice services. Another analysis showed that more than half of leukemia patients spent the whole period of their final month in hospital [16]. SPC rates of less than 20% in patients who died from acute leukemia are confirmed by other studies [17].…”
Section: Patients With Different Hematological Malignanciessupporting
confidence: 55%
See 2 more Smart Citations
“…More than 80% were hospitalized in the last 30 days of their life and only a minority of them had received palliative care or hospice services. Another analysis showed that more than half of leukemia patients spent the whole period of their final month in hospital [16]. SPC rates of less than 20% in patients who died from acute leukemia are confirmed by other studies [17].…”
Section: Patients With Different Hematological Malignanciessupporting
confidence: 55%
“…Retrospective studies, describing their experiences with different models of integrated SPC in daily clinical practice in patients with HM, report rates of 30-50% of patients who had at least 1 referral to SPC [16,20,21]. SPC seems to be more frequent in patients dying at home and with a longer course of disease, but is not dependent on age or gender [20,21].…”
Section: Experiences With Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Collaboration between hematology and a PC team has had demonstrated success in symptom management, alleviation of psychosocial burden imposed by hematological cancer and its treatment, discussion of advance care planning, home care provision, enhancement of hospice transfer during end of life, and bereavement support for family members. 7,8 Even at an advanced stage of disease, patients may still benefit from anticancer treatment (including chemotherapy and adjuvants such as high-dose steroids). As well, patients may have high dependency on blood products and be predisposed to different infectious complications.…”
Section: Optimizing End-of-life Care For Patients With Hematological mentioning
confidence: 99%
“…There are special considerations for hematology patients with regard to PC such as the rapid change to a terminal trajectory, whether to include the administration of blood products during end-of-life care, and management of various infectious complications. 7 However, these challenges can be addressed by a proactive hematology subculture with a positive attitude toward the integration of PC. Primary PC in the form of excellent communication about treatment options, prognosis, and attention to symptom management can be provided by the primary hematological oncology team when staff members all have appropriate training and skills.…”
Section: Optimizing End-of-life Care For Patients With Hematological mentioning
confidence: 99%